Fornix reconstruction with amniotic membrane transplantation: A cosmetic remedy for blind patients - Shreya Thatte; Jagriti Jain (Journal of Ophthalmic & Vision Research, 2016)
Purpose: Fornix contracture is an obstacle for fitting a prosthesis in blind or enucleated patients, and may lead to disfigurement and psychological issues. This study evaluates the efficacy of amniotic membrane transplantation (AMT) for fornix reconstruction with the aim of better retention of the ocular prosthesis. Methods: This non-comparative interventional case series includes eighteen blind eyes with fornix deformity in which a cosmetic prosthesis could not be retained. Various causative factors included symblepharon, cyst formation and fornix shortening after enucleation. AMT was performed along with correction of symblepharon, cicatrix release, and excision of the cyst with or without anchoring sutures to reform the fornix. Results: Mean fornix depth pre- and post-operation were 3.72 ± 0.69 and 7.13 ± 0.81 mm, respectively. Fornix deepening was achieved successfully in 15 cases (83.33%). Partial success was achieved in 1 case (5.66%); the remaining two cases (11.11%) were considered as failure despite repeat surgery. Both of these patients suffered from extensive symblepharon formation. Satisfactory results, i.e. formation of a deep fornix to hold the ocular prosthesis, could be achieved in 16 (89.99%) cases. There were no serious complications such as infection or graft rejection. Conclusion: AMT can be a viable option for fornix reconstruction. It has a high success rate in subjects with blind eyes and moderate fornix shortening who are unable to retain an ocular prosthesis.